Механіко-технологічні передумови зменшення втрат маси коренеплодів в процесі їх збирання - Адамчук, В. В.; Борис, А. М.; Булгаков, В. М.; Борис, М. М.; Adamchuk, V.; Borys, А.; Bulgakov, V.; Borys, M. (КНТУ, 2015)
Метою досліджень є зменшення втрат цукроносної маси в процесі відділення гички цукрових буряків від головок коренеплодів. В результаті експериментального дослідження розподілення висоти виступання головок коренеплодів над поверхнею ґрунту підтверджена гіпотеза про те, що воно не заперечує закону нормального розподілення. По результатах проведених вимірювань встановлені межі змін його статистичних характеристик, які мають наступні значення: середньостатистичне відхилення σ = 20...30 мм, математичне сподівання m = 40...60 мм. Розроблена лабораторна установка і проведені на ній експериментальні дослідження дали всі основи для розроблення нової системи автоматичного корегування висоти зрізу гички на коренезбиральних машинах сучасного технічного рівня. The experimental results and performance testing process sugar beet conducted in recent years have shown that the beet modern machines that were produced in Europe and America, working with significant losses on sugar mass. These losses are due to generally poor quality cut tops with bits of sugar beet in the bud. Therefore, now is the urgent search for technical solutions that will avoid these losses. The purpose of research is to reduce the losses of sugar supply in the process of separating the tops of the heads of sugar beet roots. As a result of the experimental investigation of the distribution of height protruding heads of root crops above the ground confirmed the hypothesis that it can not deny the law of normal distribution. The results of the measurements set limits changes in its statistical characteristics, which are as follows: average statistical deviation σ = 20 ... 30 mm, the expectation m = 40 ... 60 mm. Designed and conducted laboratory setting her experimental studies have every reason to develop a new system of automatic cor.
Mechanics and technology background reduce losses weight of root during their harvesting
Keywords: цукрові буряки; збиральні машини; втрати; цукроносна маса; статистичне розподілення; висота виступання; sugar beet harvesters; loss; weight sugar; the statistical distribution; of the height of protrusion